Workplace Mistreatment: A Qualitative Study of the Antecedents of Supervisor-Employee Relationship Challenges - Grimwood, Kim (Graduate School of Business (GSB), 2023)
This research aims to explore the phenomena of aggression in the workplace, its context, and its antecedents, with a particular focus on the impact the supervisor has on the employee in this situation. The study is located in the workplace mistreatment arena, and because it looks at the relationship between the employee and supervisor, the abusive supervision arena, in particular. The phenomenon of abusive supervision was established around 2003 and since, for the last 20 years, has been researched, with numerous academic studies contributing to its now fairly well established sub-category within workplace mistreatment. With around 20 years of work experience in the corporate financial arena, the researcher has observed this phenomenon at certain times, not applied only to herself, but also to others in the workplace. The interest in this research stems from this observation. The primary research question of this study is: What are the perceived reasons the supervisor behaves aggressively towards the employee? This study aims to contribute to the field of workplace mistreatment - and abusive supervision – through employing an inclusive innovation approach, and accessing participants in a financial institution, using a qualitative approach for extraction of antecedents, from the Global South region (South Africa in particular). The research for this study was conducted using sixteen participants in individual ninety minute interviews. Further, it was executed using a video conferencing tool, and interviews were held with employees from one of the largest financial institutions in South Africa (with around 7,000 employees). The participants ranged in age, gender, race, work tenure, and role sizing (position). The participants contributed by exploring the challenges and causes of the supervisor-employee relationship from both the supervisor's and the employee's perspectives. A thematic analysis was done on the data collected, and four central themes emerged. These themes revolved around the four principal parties within the organisation: the supervisor, the employee, the leaders, and the team. There are three key categories used in describing the reasons the supervisor behaves aggressively, as pertains to the literature on abusive supervision. These are the threats faced by the supervisor from within, the threats from below and the threats from above. The research findings of this study corroborated core points in these three categories. In particular, that the supervisor falls prey to being overwhelmed by an inability to cope (threats from within), and that they are also vulnerable to envy and the use of power dynamics as a tool of engagement where employee differences exist (threats from below). In addition, they are often obliged to serve the demands of senior leadership (threats from above). The new insights this research brings is to present additional causes under each of the three existing threats. This research, in addition, presents a fourth threat that should be considered under abusive supervision. This additional category of threat has been labelled “threats from around”. This relates to the threat that presents itself to the supervisor from the team members themselves. The influence the teams have on the relationship between the supervisor and employee in the work environment, includes dynamics within the team that impact the supervisor, which includes gossip, overt competitiveness, bullying and the effect a powerful minority has on the supervisor. This research shows that it is a key cause of conflict to be considered when exploring the relationship, particularly the aggressive tendencies, between the supervisor and employee. Overall, the research process produced many insights, and its conclusion was that the supervisor impacts the employee, but not in isolation; leaders and teams are accountable here also. Recommendations for further study include that the additional causes presented under each threat and the threat from around should be further corroborated. Further qualitative studies should be undertaken using the qualitative method presented in this study but also applied to the Global North, using financial institutions where possible. Additional research into the following particularly interesting elements may result in an even deeper understanding of the problem: the (mis)use of power in the context of workplace mistreatment; the presence of envy and immaturity; the role of training and clarity of communication; the impact of manipulation in the promotional process; the lack of timeous empowerment of employees, and evasive leaders. It is the hope of the researcher that this study will be enjoyed, but also taken and used to enhance the broader field and ultimately to drive a solution. One such solution, a proposed praxis model, is presented in this study, and aims to show how to, practically, help those experiencing these phenomena in the workplace. Ultimately, the hope is that one day workplace mistreatment, and abusive supervision, will be phenomena about which those in the workplace will be well-informed and with which they will be well-equipped to deal with appropriately. Thereby moving one step closer to achieving greater peace and joy within the workplace.